Whole-Genome Sequencing of Acer catalpifolium Reveals Evolutionary History of Endangered Species. (8th December 2021) - Yu, Tao; Hu, Yiheng; Zhang, Yuyang; Zhao, Ran; Yan, Xueqing; Dayananda, Buddhi; Wang, Jinpeng; Jiao, Yuannian; Li, Junqing; Yi, Xin
Abstract: Acer catalpifolium is an endangered species restricted to remote localities of West China. Understanding the genomic content and evolution of A. catalpifolium is essential to conservation efforts of this rare and ecologically valuable plant. Here, we report a high-quality genome of A. catalpifolium consisting of ∼654 Mbp and ∼35, 132 protein-coding genes. We detected 969 positively selected genes in two Acer genomes compared with four other eudicots, 65 of which were transcription factors. We hypothesize that these positively selected mutations in transcription factors might affect their function and thus contribute to A. catalpifolium' s decline-type population. We also identified 179 significantly expanded gene families compared with 12 other eudicots, some of which are involved in stress responses, such as the FRS–FRF family. We inferred that A. catalpifolium has experienced gene family expansions to cope with environmental stress in its evolutionary history. Finally, 109 candidate genes encoding key enzymes in the lignin biosynthesis pathway were identified in A. catalpifoliu m; of particular note were the large range and high copy number of cinnamyl alcohol dehydrogenase genes. The chromosome-level genome of A. catalpifolium presented here may serve as a fundamental genomic resource for better understanding endangered Acer species, informing future conservation efforts.